1996
DOI: 10.1577/1548-8659(1996)125<0690:sdacos>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Summer Distribution and Condition of Striped Bass within Albemarle Sound, North Carolina

Abstract: During 1993–1994, 78 adult striped bass Morone saxatilis captured in the Albemarle Sound–Roanoke River (AR) system were tagged with ultrasonic transmitters to examine summer patterns of distribution, migration, and habitat selection. Additionally, 626 striped bass were collected by electrofishing during 1993 to assess summer condition. Water temperatures within Albemarle Sound rose well above suitable levels for striped bass, but dissolved oxygen remained within tolerance limits. No stratification of temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 26 publications
0
53
0
Order By: Relevance
“…However, fi sheries-independent data indicate that it is predominantly the large Striped Bass of the AR stock that migrate to ocean waters. In a mobile telemetry study, Haeseker et al (1996) searched the Albemarle Sound during summer (May-August) for the presence of 26 telemetered Striped Bass (all but 1 fi sh <600 mm TL) that participated in the April Roanoke River spawning run. They relocated 25 (96%) of these fi sh in the Albemarle Sound at least 1 month after spawning, providing evidence that smaller Striped Bass mostly remain in the estuary after spawning.…”
Section: Caveatsmentioning
confidence: 99%
“…However, fi sheries-independent data indicate that it is predominantly the large Striped Bass of the AR stock that migrate to ocean waters. In a mobile telemetry study, Haeseker et al (1996) searched the Albemarle Sound during summer (May-August) for the presence of 26 telemetered Striped Bass (all but 1 fi sh <600 mm TL) that participated in the April Roanoke River spawning run. They relocated 25 (96%) of these fi sh in the Albemarle Sound at least 1 month after spawning, providing evidence that smaller Striped Bass mostly remain in the estuary after spawning.…”
Section: Caveatsmentioning
confidence: 99%
“…Within estuaries, temperature influences nonspawning striped bass distribution (Coutant and Benson 1990;Bjorgo et al 2000;Able and Grothues 2007;Ng et al 2007;Wingate and Secor 2007). In many estuaries, striped bass concentrate near shorelines (Ng et al 2007), structures (Haeseker et al 1996), creek mouths (Waldman et al 1990;Tupper and Able 2000), and other complex habitats (confluences, mussel beds; Harding and Mann 2003). Striped bass are generalist feeders that consume forage fish and invertebrates (Hartman and Brandt 1995;Ferry 2003;Nelson et al 2003;Walter et al 2003).…”
Section: Patterns Of Within-estuary Distributionmentioning
confidence: 99%
“…These studies show that after the spawning season, Atlantic striped bass migrate north along the coast before returning south in the fall to the area where they overwinter (Boreman and Lewis 1987;Waldman et al 1990). Recent acoustic telemetry studies of other coastal populations (Haeseker et al 1996;Carmichael et al 1998;Bjorgo et al 2000) provide multiple detection data on individual striped bass that inhabit coastal systems. These fish, however, do not typically move long distances north-south along the coast.…”
mentioning
confidence: 99%
“…Staples and glue (cyanoacrylate) were easy to place and reduced handling and anesthetic time [18][19][20]; though, each had limitations. Studies using staples have reported good incision healing [19]; however, other studies have reported increased mortality and transmitter expulsion [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Staples and glue (cyanoacrylate) were easy to place and reduced handling and anesthetic time [18][19][20]; though, each had limitations. Studies using staples have reported good incision healing [19]; however, other studies have reported increased mortality and transmitter expulsion [20,21]. Cyanoacrylate was reported to successfully close incisions; yet some studies indicated that wounds dehisced, and the occurrence of tissue inflammation and necrosis increased [7,22,23].…”
Section: Introductionmentioning
confidence: 99%